Effect of Sun-exposure before Moisture-yellowing on the Aroma of Yellow Tea - Xinying CHEN; Junran QI; Lixia ZHANG (Shipin gongye ke-ji)
To further elucidate the impact of “sun-exposure” and “moisture-yellowing” as well as their interaction, based on low-temperature treatment of fresh leaves, on the aroma quality of yellow tea, this paper used fresh tea leaves with a bud and one leaf picked from ‘Jin Xuan’ variety and then treated at a low temperature of 5 ℃ for 18 h as raw material. Different durations of sun-exposure before moisture-yellowing, moisture-yellowing, and their combined processing techniques were set up. The tea samples were analyzed by the sensory evaluation and headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) methods. The results showed that the optimal quality of yellow tea was obtained by sun-exposure to the leaf for 0.5 hours under the environmental conditions of light intensity 1700±50 μmol∙m−2∙s−1, outdoor temperature 35±5 ℃, and air humidity 30%±5%, and then moisture-yellowing for 3 hours at a temperature of 45 ℃ and humidity of 70%. Compared with the control tea sample that was only moisture-yellowing for 3 hours, the optimal tea sample increased the total amount of aroma substances by 91.26%. The contents of sweet, floral, and fruity aroma compounds such as ketones, aldehydes, alcohols, and esters were 6.18, 5.55, 3.79, and 2.99 times that of the control sample, respectively. Meanwhile, the content of sulfur-containing components with green fragrance was reduced by 26.72%. The results led to the enhancement of the aroma concentration of 'Jin Xuan' yellow tea and promoted the transformation of its fragrance type. At the same time, there was an interaction between sun-exposure and moisture-yellowing. On the one hand, sun-exposure could effectively shorten the duration of moisture-yellowing, and on the other hand, moisture-yellowing was also conducive to removing the fishy smell that may be brought by sun-exposure and also further promoted the improvement of the aroma quality of 'Jin Xuan' yellow tea.